2015
DOI: 10.1002/ptr.5445
|View full text |Cite
|
Sign up to set email alerts
|

Olive Leaf Extract Improves the Atherogenic Lipid Profile in Rats Fed a High Cholesterol Diet

Abstract: Coronary heart disease because of atherosclerosis is still the most common cause of mortality. Elevated levels of low-density lipoprotein and total cholesterol are major risk factors for atherosclerotic cardiovascular disease. The aim of this study was to evaluate the effects of the olive leaf extract on serum lipid profile, early changes of atherosclerosis and endothelium-dependent relaxations in cholesterol-fed rats. For this purpose, rats were fed by 2% cholesterol-enriched or standard chow for 8 weeks. Som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 27 publications
2
15
0
1
Order By: Relevance
“…The serum obtained was used to estimate the triacylglycerides (TAGs), total cholesterol (TC), and high‐density lipoprotein (HDL), which were determined by enzymatic methods with an automatic analyzer (Diamond Biodiagnostic ©, Hannover, Germany). Low and very low‐density lipoprotein (LDL, vLDL) and atherogenic index of plasma (AIP) were calculated according to Olmez et al (). Also, the enzymatic parameters (Alanine aminotransferase—ALT; aspartate aminotransferase—AST; aspartate transaminase—ALP), albumin and bilirubin were measured using commercial assay kits (Randox laboratories ©, San Francisco CA, USA) according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The serum obtained was used to estimate the triacylglycerides (TAGs), total cholesterol (TC), and high‐density lipoprotein (HDL), which were determined by enzymatic methods with an automatic analyzer (Diamond Biodiagnostic ©, Hannover, Germany). Low and very low‐density lipoprotein (LDL, vLDL) and atherogenic index of plasma (AIP) were calculated according to Olmez et al (). Also, the enzymatic parameters (Alanine aminotransferase—ALT; aspartate aminotransferase—AST; aspartate transaminase—ALP), albumin and bilirubin were measured using commercial assay kits (Randox laboratories ©, San Francisco CA, USA) according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…were calculated according to Olmez et al (2015). Also, the enzymatic parameters (Alanine aminotransferase-ALT; aspartate aminotransferase-AST; aspartate transaminase-ALP), albumin and bilirubin were measured using commercial assay kits (Randox laboratories ©, San Francisco CA, USA) according to the manufacturer's instructions.…”
Section: Collection Of Blood Samplesmentioning
confidence: 99%
“…Several recent studies demonstrated that consumption of plant extracts decreases the level of LDL, an important factor for cardiovascular diseases. Increased level of cholesterol results in atherosclerosis due to the increased lipid peroxidation [1416]. Thus, LDL peroxidation is an important target for the prevention of atherosclerosis and can be prevented by antioxidants.…”
Section: Discussionmentioning
confidence: 99%
“…Sonuç olarak zeytin yaprağı ekstresinin aterosklerozda olumlu etkilerinin olabileceği belirtilmiştir. 33 Zeytin yaprağının östrojen eksikliğinden kaynaklanan dislipidemi tablosunu iyileştirdiği hipotezi ile overektomili ratlar üzerinde yapılan bir çalışmada, 10 hafta boyunca 200-400 mg/kg zeytin yaprağı ekstresi verilen ratlarda alım süresi sonunda kontrol grubu ile karşılaştırıldığında serum trigliserid ve VLDL seviyelerinde anlamlı bir azalma olduğu gözlenmiş ancak LDL düzeyinin değişmediği belirtilmiştir. Ayrıca yüksek dozda zeytin yaprağı ekstresi alımının serum östradiol seviyesini anlamlı ölçüde arttırdığı belirtilmiştir.…”
Section: Somova Ve Arknın (2003) Yaptığı Bir çAlışmadaunclassified